1980
DOI: 10.1002/1097-0142(19800615)45:12<3086::aid-cncr2820451234>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Denial and helplessness in cancer patients undergoing radiation therapy: Sex differences and implications for prognosis

Abstract: One hundred consecutive outpatients undergoing radiation therapy were prospectively studied using the Locus of Control Inventory designed by Rotter and a questionnaire covering various aspects of diagnosis, implications of disease, and details of therapy. The Locus of Control Inventory, which measures a person's belief that life's important events are controlled by personal effort (internality) as opposed to factors outside of one's control (externality), revealed a significant difference between men and women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 8 publications
2
17
0
1
Order By: Relevance
“…This finding is concordant with studies among patients with other cancer types and coronary heart disease [54][55][56][57]. Traditionally, men are found to be more focused on work-related issues and women on family and health-related matters [58].…”
Section: Background Factorssupporting
confidence: 86%
“…This finding is concordant with studies among patients with other cancer types and coronary heart disease [54][55][56][57]. Traditionally, men are found to be more focused on work-related issues and women on family and health-related matters [58].…”
Section: Background Factorssupporting
confidence: 86%
“…This proposal is supported by Thompson et al (1998), who found no difference between the genders regarding sense of control over age-related physical changes. However, in the case of cancer, women have been reported to express less control than men do (Leigh et al, 1980;Nolen-Hoeksema et al, 1999). In general, cancer prevalence is similar among both genders, whereas heart diseases are often perceived as men's related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, differences in personality traits were examined in people from 37 nations, and women scored higher in neuroticism in all nations (Lynn & Martin, 1997). Women cancer patients express less control than men do (Leigh, Ungerer & Percarpio, 1980;NolenHoeksema et al, 1999). Women appear to be more emotionally vulnerable and express more types of negative emotions (Bekker, Croon, & Vermaas, 2002;Senior, Weinman, & Marteau, 2002;Smith & Reise, 1998;Vassend & Skrondal, 1999).…”
mentioning
confidence: 99%
“…Parmi les facteurs comportementaux et environnementaux, certains auteurs soulignent l'impact du style de vie des hommes : consommation d'alcool et de tabac, mauvaises habitudes alimentaires, prises de risque délibérées [3,12,26,48], des conditions de travail plus difficiles [42], un intérêt moins marqué pour l'information sanitaire [4] ou encore le fait que ceux-ci attendraient davantage avant d'avoir recours aux soins [23,36]. Ces comportements à risques pourraient être expliqués par certains facteurs individuels dispositionnels (traits de personnalité) et transactionnels (croyances, stratégies d'ajustement) plus marqués chez les hommes comme le sentiment d'invulnérabilité, la minimisation des risques [23] ou le déni de la maladie [2,9,33].…”
Section: Introductionunclassified